OSTEOCALCIN GENE POLYMORPHISM IN INDONESIAN MEN WITH PERIODONTITIS - KAULIKA, NAMIRA; ALWASRIS, TALITHA; DJAMAL, NINIARTI; SULIJAYA, BENSO; TALBOT, CHRISTOPHER; AUERKARI, ELZA IBRAHIM (International Journal of Applied Pharmaceutics, 2020)
Objective: Through this work, we aimed to clarify the association between the severity of periodontitis and osteocalcin (OC) gene C298T polymorphism in Indonesian male subjects. Methods: DNA was extracted from blood serum samples of 100 consenting Indonesian men whose periodontitis was classified as mild, moderate, or severe. Polymerase chain reaction and restriction fragment length polymorphism techniques were applied to evaluate the status of OC (C298T) polymorphism using HindIII restriction enzyme and electrophoresis in agarose gel to separate the indicated fragments. Results: Although genotype distribution of the OC C298T polymorphism showed a trend for more frequent occurrence of genotype hh (and allele h) with increasing severity of periodontitis, this trend was not statistically significant in the tested sample population, in whom the HH genotype appeared to be relatively rare. Conclusion: The results showed no significant association between the severity of periodontitis and OC C298T polymorphism in Indonesian male subjects.